Blood group AB increases risk for surgical necrotizing enterocolitis and focal intestinal perforation in preterm infants with very low birth weight - I. Martynov (Nature Portfolio, 2021)
Abstract Necrotizing enterocolitis (NEC) and focal intestinal perforation (FIP) are two of the most common emergencies of the gastrointestinal tract in preterm infants with very low birth weight (VLBW, birth weight < 1500 g). Identification of risk factors among these children is crucial for earlier diagnosis and prompt intervention. In this study, we investigated a relationship between ABO blood groups and the risk for surgical NEC/FIP. We genotyped the ABO locus (rs8176746 and rs8176719) in VLBW infants enrolled in a prospective, population-based cohort study of the German Neonatal Network (GNN). Of the 10,257 VLBW infants, 441 (4.3%) had surgical NEC/FIP. In univariate analyses, the blood group AB was more prevalent in VLBW infants with surgical NEC/FIP compared to non-AB blood groups (OR 1.51, 95% CI 1.07–2.13, p = 0.017; absolute risk difference 2.01%, 95% CI 0.06–3.96%). The association between blood group AB and surgical NEC/FIP was observed in a multivariable logistic regression model (OR of 1.58, 95% CI 1.10–2.26, p = 0.013) as well. In summary, our study suggests that the risk of surgical NEC and FIP is higher in patients with blood group AB and lower in those having non-AB blood groups.